Peran Analisis Swot dalam Pengambilan Keputusan Strategis pada Usaha Warcaf - Etty Zuliawati Zed; Angelica Juliana Della; Nurima Rahmawati; Rahil Nurfadhilah; Indira Oktavia (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
This study aims to investigate the role of SWOT analysis in the strategic decision-making process at Warcaf, Warcaf is a business operating in the culinary sector. In the context of increasingly tight business competition today, it is very important for a company to have a good strategy in order to remain competitive in the market. SWOT analysis, including the recognition of strengths, weaknesses, opportunities, and threats, serves as a fairly efficient instrument in designing strategies that are in accordance with the company's internal and external situations. The method applied in this study is a qualitative approach, where information is obtained through in-depth interviews with Warcaf management. This study shows that SWOT analysis not only plays a role in the strategic decision-making process, but also as a basis for long-term planning. It is expected that this study can provide contributions such as information and strategies in the culinary industry.